Increased prevalence of the COVID-19 associated Neanderthal mutations in the Central European Roma population - Jaroslav A. Hubáček; Lenka Šedová; Věra Hellerová; Věra Adámková; Valérie Tóthová (Taylor & Francis Group, 2024)
AbstractBackground Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and subsequent COVID-19 has spread world-wide and become pandemic with about 7 million deaths reported so far. Interethnic variability of the disease has been described, but a significant part of the differences remain unexplained and may be attributable to genetic factors.Aim To analyse genetic factors potentially influencing COVID-19 susceptibility and severity in European Roma minority.Subjects and methods Two genetic determinants, within OAS-1 (2-prime,5-prime-oligoadenylate synthetase 1, a key protein in the defence against viral infection; it activates RNases that degrade viral RNAs; rs4767027 has been analysed) and LZTFL1 (leucine zipper transcription factor-like 1, expressed in the lung respiratory epithelium; rs35044562 has been analysed) genes were screened in a population-sample of Czech Roma (N = 302) and majority population (N = 2,559).Results For both polymorphisms, Roma subjects were more likely carriers of at least one risky allele for both rs4767027-C (p < 0.001) and rs35044562-G (p < 0.00001) polymorphism. There were only 5.3% Roma subjects without at least one risky allele in comparison with 10.1% in the majority population (p < 0.01).Conclusions It is possible that different genetic background plays an important role in increased prevalence of COVID-19 in the Roma minority.